Insights of health district managers on the implementation of primary health care outreach teams in Johannesburg, South Africa: a descriptive study with focus group discussions. Issue 1 (December 2017) - Moosa, Shabir; Derese, Anselme; Peersman, Wim
Abstract Background Primary health care (PHC) outreach teams are part of a policy of PHC re-engineering in South Africa. It attempts to move the deployment of community health workers (CHWs) from vertical programmes into an integrated generalised team-based approach to care for defined populations in municipal wards. There has little evaluation of PHC outreach teams. Managers' insights are anecdotal. Methods This is descriptive qualitative study with focus group discussions with health district managers of Johannesburg, the largest city in South Africa. This was conducted in a sequence of three meetings with questions around implementation, human resources, and integrated PHC teamwork. There was a thematic content analysis of validated transcripts using the framework method. Results There were two major themes: leadership-management challenges and human resource challenges. Whilst there was some positive sentiment, leadership-management challenges loomed large: poor leadership and planning with an under-resourced centralised approach, poor communications both within the service and with community, concerns with its impact on current services and resistance to change, and poor integration, both with other streams of PHC re-engineering and current district programmes. Discussion by managers on human resources was mostly on the plight of CHWs and calls for formalisation of CHWs functioning and training and nurse challenges with inappropriate planning and deployment of the team structure, with brief mention of the extended team. Conclusions Whilst there is positive sentiment towards intent of the PHC outreach team, programme managers in Johannesburg were critical of management of the programme in their health district. Whilst the objective of PHC reform is people-centred health care, its implementation struggles with a centralising tendency amongst managers in the health service in South Africa. Managers in Johannesburg advocated for decentralisation. The implementation of PHC outreach teams is also limited by difficulties with formalisation and training of CHWs and appropriate task shifting to nurses. Change management is required to create true integrate PHC teamwork. Policy review requires addressing these issues.